2021
DOI: 10.1177/09544062211024688
|View full text |Cite
|
Sign up to set email alerts
|

A novel nonlocal higher-order theory for the accurate vibration analysis of 2D FG nanoplates

Abstract: In this paper, vibration analysis of the 2 D-FG nanoplate is studied based on a novel higher-order shear deformation theory (HSDT). The proposed HSDT is a composition of trigonometric, exponential and polynomial functions which is one of the most accurate HSDTs. The mechanical properties of the nanoplate change along with the length and thickness directions, according to arbitrary functions. To model the displacement field, the impacts of both transverse shear and thickness stretching are considered. To consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Their results showed that the hardness of the structure increases with the increase of the parameter of length scale of the material. Xie et al 7 studied a novel nonlocal higher-order theory for the accurate vibration analysis of 2D FG nanoplates. The results illustrate that when size effect parameter is smaller/greater than 0.5 nm, the impacts of the FG parameters on the frequency of the system increase/reduce.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the hardness of the structure increases with the increase of the parameter of length scale of the material. Xie et al 7 studied a novel nonlocal higher-order theory for the accurate vibration analysis of 2D FG nanoplates. The results illustrate that when size effect parameter is smaller/greater than 0.5 nm, the impacts of the FG parameters on the frequency of the system increase/reduce.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the assumptions of simple inverse hyperbolic shear deformation theory and nonlocal elasticity theory, Pun-Van et al [44] mathematically modeled the isogeometric approach on free vibrations of GPLRC. Xie et al [45] proposed a novel nonlocal higher-order theory to obtain accurate vibration properties of 2D functionally graded nanoplates.…”
Section: Introductionmentioning
confidence: 99%
“…After that, plenty of researches are accomplished to analyse the bending, buckling, and vibration response of distinct nano-structures such as nano sized beams, plates, and shells using this theory. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Researchers have also used the nonlocal theory to study the cracks in the macro-structures. 34 Recently, Van et al 35 presented a size-dependent refined plate theory and studied the bending and vibrations of graphenereinforced composite nano-plates with different types of gradation of graphene platelets.…”
Section: Introductionmentioning
confidence: 99%